Analysis Unhealthy Business Competition in the Business Era Digital Based - Latifah, Aliah; Husen, La Ode; Jasmaniar, Jasmaniar (ADVANCED PRIVATE LEGAL INSIGHTS, 2025)
The purpose of this research is to understand and analyze the regulation of unfair business practices in the digital business era in Indonesia, as well as the impact of unfair competition on innovation and business sustainability in the future. This research employs a normative research method, using primary and secondary legal materials obtained through literature and the analysis of books, journals, and cases, particularly those available on the internet, literature books, and laws. The research results indicate that unfair competition in Indonesia is regulated by the ITE Law No. 11 of 2008 and Law no. 5 of 1999, but there are still gaps in oversight, especially in the digital sector. The ITE Law focuses more on electronic transactions and personal data protection, while the Anti-Monopoly Law has not fully accommodated new challenges such as predatory pricing and market dominance by large platforms. As a result, unfair competition can lead to market monopolies, a decrease in MSME turnover, and future losses for consumers. The research recommendation is that the anti-monopoly law has been effective in reducing unfair competition in the digital sector, but the government needs to provide further support, especially regarding the limitations of the KPPU under the existing regulations, without disrupting existing industries. Also, to prevent the negative impacts of unfair competition, tighter oversight is necessary, especially in competition within the digital sector, such as e-commerce.